RNA Cleavage Catalyzed by Amphoteric Bis(acyl)guanidinium Derivatives. Issue 2 (February 2014) - Göbel, Michael W.; Roussev, Christo D.; Scheffer, Ute
Abstract Described herein are two series (twelve compounds each) of very closely related guanidinium‐based receptors and their ability to catalyze hydrolytic cleavage of a unique RNA substrate – oligo‐dT flanked trans‐Activation Responsive region of the HIV‐1 mRNA, TAR RNA. The significant difference in activities of otherwise very similar compounds is discussed, and direct and indirect evidences supporting our interpretation are presented. The results indicate that improvements in catalytic efficiency could be achieved with little modification of the structure of a relatively weak catalyst, and that a crucial feature could be a finely calibrated interplay between anion‐binding and proton‐donating abilities.